Cross-reactivity between histone demethylase inhibitor valproic acid and DNA methylation in glioblastoma cell lines - Barciszewska, Anna-Maria; Belter, Agnieszka; Gawrońska, Iwona; Giel-Pietraszuk, Małgorzata; Naskręt-Barciszewska, Mirosława Z. (Frontiers in Oncology, 2022)
Currently, valproic acid (VPA) is known as an inhibitor of histone deacetylase (epigenetic drug) and is used for the clinical treatment of epileptic events in the course of glioblastoma multiforme (GBM). Which improves the clinical outcome of those patients. We analyzed the level of 5-methylcytosine, a DNA epigenetic modulator, and 8-oxodeoxyguanosine, an cellular oxidative damage marker, affected with VPA administration, alone and in combination with temozolomide (TMZ), of glioma (T98G, U118, U138), other cancer (HeLa), and normal (HaCaT) cell lines. We observed the VPA dose-dependent changes in the total DNA methylation in neoplastic cell lines and the lack of such an effect in a normal cell line. VPA at high concentrations (250-500 μM) induced hypermethylation of DNA in a short time frame. However, the exposition of GBM cells to the combination of VPA and TMZ resulted in DNA hypomethylation. At the same time, we observed an increase of genomic 8-oxo-dG, which as a hydroxyl radical reaction product with guanosine residue in DNA suggests a red-ox imbalance in the cancer cells and radical damage of DNA. Our data show that VPA as an HDAC inhibitor does not induce changes only in histone acetylation, but also changes in the state of DNA modification. It shows cross-reactivity between chromatin remodeling due to histone acetylation and DNA methylation. Finally, total DNA cytosine methylation and guanosine oxidation changes in glioma cell lines under VPA treatment suggest a new epigenetic mechanism of that drug action.